The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/cid/ciz1147
|View full text |Cite
|
Sign up to set email alerts
|

A Parsimonious Host Inflammatory Biomarker Signature Predicts Incident Tuberculosis and Mortality in Advanced Human Immunodeficiency Virus

Abstract: Background People with advanced human immunodeficiency virus (HIV) (CD4 < 50) remain at high risk of tuberculosis (TB) or death despite the initiation of antiretroviral therapy (ART). We aimed to identify immunological profiles that were most predictive of incident TB disease and death. Methods The REMEMBER randomized clinical trial enrolled 850 participants with HIV (CD4 < 50 cells/µL) at ART initiation to rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, in our exploratory analyses, LTBI+ TB progressors had a profile more similar to LTBI− women, with higher levels of IL-1 β , IL-6, IL-13 and IL17a and generally lower levels of IFN γ compared to LTBI+ non-progressors. These inflammatory markers have been recognized for their complex role in TB disease where while a deficiency is linked to reduced control of Mtb infection, excessive levels can result in tissue damage and immunopathology ( 1 , 28 33 ) as well as progression to active TB disease in non-pregnant adults ( 34 ). Given the small number of progressors in this study, these findings will need to be confirmed in other studies with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our exploratory analyses, LTBI+ TB progressors had a profile more similar to LTBI− women, with higher levels of IL-1 β , IL-6, IL-13 and IL17a and generally lower levels of IFN γ compared to LTBI+ non-progressors. These inflammatory markers have been recognized for their complex role in TB disease where while a deficiency is linked to reduced control of Mtb infection, excessive levels can result in tissue damage and immunopathology ( 1 , 28 33 ) as well as progression to active TB disease in non-pregnant adults ( 34 ). Given the small number of progressors in this study, these findings will need to be confirmed in other studies with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no difference was observed in sCD14, IL-8 and Th1/Th2/Th17 cytokines between patients who died or were discharged. Biomarker concentrations are observable outcomes of complex biological processes that are only partially understood, and this may be the reason for a lack of consensus regarding immunological markers in prediction of mortality in HIV/AIDS patients [30][31][32][33][34] . Curiously, we observed much higher levels of in ammatory biomarkers sCD14, IL-8, and IL-6 than for other cytokines, which is consistent with the in ammatory status of the HIV/AIDS patients 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Host-based markers are extensively being explored to improve predictive and diagnostic tools for IRIS in PLWH who have a concomitant OI [ 104 , 136 , 137 , 138 , 139 , 140 ]. In this context, several host factors have been studied as an IRIS predictive tool, including genetic markers, immune metabolomic and biomarkers of SI ( Table 1 ).…”
Section: Use Of Host Markers To Predict Irismentioning
confidence: 99%